2018
DOI: 10.3390/md16100388
|View full text |Cite
|
Sign up to set email alerts
|

For a Correct Application of the CD Exciton Chirality Method: The Case of Laucysteinamide A

Gennaro Pescitelli

Abstract: The circular dichroism (CD) exciton chirality method (ECM) is a very popular approach for assigning the absolute configuration (AC) of natural products, thanks to its immediacy and ease of application. The sign of an exciton couplet (two electronic CD bands with opposite sign and similar intensity) can be directly correlated with the molecular stereochemistry, including the AC. However, a correct application of the ECM necessitates several prerequisites: knowledge of the molecular conformation; knowledge of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Adapted from ref. 55 sought to solve stereochemical problems in the most suitable way, also based on the ECM. 97 The important message from the case of acyclic 1,2and 1,3-diols is that, in the presence of flexible bis(chromophoric) compounds, one cannot infer the AC without knowing, or at least making a hypothesis, on the molecular conformation.…”
Section: Ecm Of Flexible Compounds: a Challenge From Conformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted from ref. 55 sought to solve stereochemical problems in the most suitable way, also based on the ECM. 97 The important message from the case of acyclic 1,2and 1,3-diols is that, in the presence of flexible bis(chromophoric) compounds, one cannot infer the AC without knowing, or at least making a hypothesis, on the molecular conformation.…”
Section: Ecm Of Flexible Compounds: a Challenge From Conformationmentioning
confidence: 99%
“…Because we considered the case of laucysteinamide A a very pertinent educational example to highlight the procedure for a correct application of the ECM, we run before a complete structural and electronic analysis by DFT and TD-DFT methods. 55 Here, we only briefly summarize the main results: F I G U R E 8 (A-C) Allylic benzoate method applied to a cholest-4-en-3β-ol benzoates (10). The shaded region in (B) is normally not accessible experimentally or obscured by other bands.…”
Section: Mistaken Ndec: Laucysteinamide a As An Illustrative Examplementioning
confidence: 99%
“…For the ( R ) configuration, the two transition dipoles define a positive chirality (that is, a clockwise rotation is necessary to move the dipole in the front onto that in the back, shown in Figure ), which is in accord with the positive couplet found for (+)‐ 1 . It must be stressed that a correct application of the exciton chirality method necessitates various prerequisites to be met, the most important of which is, in the current case, an accurate knowledge of the transition moment directions. These latter (depicted in Figure ) were easily obtained by means of quick TDDFT calculations on the relevant chromophores (see details in Section 2.6).…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic data of 4: X-ray quality crystals were acquired by slow volatilization of a solvent mixture of MeOH and CH 2 Cl 2 . Crystal data for: C 21 Crystallographic data for compound 4 have been deposited in the Cambridge Crystallographic Data Centre with deposition number 1474260.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…40,42 The transition dipole moment that is involved in the exciton coupling in 1 and 2 is the 1 L b transition, oriented along the long axis of the naphthalene. Since TDM orientation can differ in macromolecular structures and the ECM only reliably works with proper knowledge of its orientation, as has been shown by many corrections of reported assignments, 56,57 assignment by the ECM has to be considered with caution. In substituted naphthalenes it has been shown that the TDM is oriented along the substitution axis, which in the case of 1 and 2 is further supported by the conjugation to the central phenylene and adjacent naphthalene.…”
Section: Assignment Of Absolute Configurationmentioning
confidence: 99%